DETERMINATION OF SOME SELECTED MINERAL COMPOSITIONS OF THE CAPPARIS SPINOSA PLANT FROM DIFFERENT EXTRACTS CULTIVATED IN ANBAR GOVERNORATE, IRAQ - MAJID MOHAISEN; M. M. Sirhan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Capers, or Capparis Spinosa, are perennial shrubs of the family Capparaceae that are native to the regions around the Mediterranean Sea. This study's objective was to determine the mineral content of several Capparis spinosa plant extracts in the Al-Baghdadi area of the Anbar governorate. Atomic absorption spectrophotometer was used to determine the mineral concentrations of various extracts including capper crude. High concentrations of Fe, Ca, K, Be, Zn, and Na were present in all capper crude and was also present in all capper components. Additionally, the samples had extremely low concentrations of Cu, Cr, Mn, and Ni. Minerals Cu and Cr were found in all regions of plant extracts (0.8618 to 0.2099 ppm) and (0.5710 - 0.1001 ppm), respectively, and were plentiful in the majority of capper crude, ranging from 55,696 ppm in Fe to 580 ppm in Na. From 9,468 ppm in capper crude to 4,438 ppm in alkaloid extract precipitate, the amount of calcium varies. The alkaloid extract filtrate had to Be concentrations in the capper crude ranging from 668 ppm to 3,770 ppm. Compared to EEF, which has a sodium content of 150 ppm, AEF has a sodium concentration of less than 344 ppm. Caper pieces were shown to be significant suppliers of nutrients and vital elements as a consequence. Additionally, it is clear that caper pieces may be used as a dietary item to provide nutrition and are an excellent source of macro- and micro-minerals.